2019
DOI: 10.1002/acr2.11100
|View full text |Cite
|
Sign up to set email alerts
|

Estimates of Responsiveness, Minimally Important Differences, and Patient Acceptable Symptom State in Five Patient‐Reported Outcomes Measurement Information System Short Forms in Systemic Lupus Erythematosus

Abstract: Objective. Examinations of Patient-Reported Outcomes Measurement Information System (PROMIS) measures in adult systemic lupus erythematosus (SLE) have provided support for their cross-sectional validity in SLE. We estimated responsiveness to change, meaningful changes (minimally important differences [MIDs]), and the patient acceptable symptom state (PASS) for five PROMIS short forms to facilitate longitudinal use and interpretation of PROMIS scales in SLE.Methods. Data from five administrations of PROMIS shor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 42 publications
2
26
0
Order By: Relevance
“…In a study comparing different anxiety self‐report tools in RA, the PROMIS Anxiety demonstrated the highest internal consistency of 0.93 and a high test‐retest reliability of 0.82 (47). Similar studies have been performed in SLE (111–117).…”
Section: Patient‐reported Outcomes Measurement Information Systemsupporting
confidence: 67%
See 2 more Smart Citations
“…In a study comparing different anxiety self‐report tools in RA, the PROMIS Anxiety demonstrated the highest internal consistency of 0.93 and a high test‐retest reliability of 0.82 (47). Similar studies have been performed in SLE (111–117).…”
Section: Patient‐reported Outcomes Measurement Information Systemsupporting
confidence: 67%
“…In this study, they compared the differences in change between different measures and found mental health domains, such as mental global health and anxiety, had smaller changes when compared with those in the physical health domains, which is consistent with results from studies of legacy instruments assessing those same domains (102). The responsiveness of the PROMIS Anxiety was also demonstrated in studies of SLE (112,131) and osteoarthritis (132). Studies have also shown that the PROMIS can discriminate between clinical groups, suggesting its suitability for use in clinical trials and comparative effectiveness studies (118,128–130,133–135).…”
Section: Patient‐reported Outcomes Measurement Information Systemmentioning
confidence: 92%
See 1 more Smart Citation
“…In an SLE cross‐sectional study, a distribution‐based estimate of the MID was approximately 4 points, and anchor‐based estimates of the MID were 2 points for worsening and 1 to 2 points for improvement (119). Other PROMIS measures not measuring sleep had MIDs that varied from 2 to 3 points (120–122).…”
Section: Promis Sleep Disturbance and Sleep‐related Impairmentmentioning
confidence: 99%
“…Psychometric properties of PROMIS sleep measures have been assessed in RA (115,118), SLE (116,119), scleroderma (112), cancer (124,125), and elderly populations (123). Additionally, PROMIS sleep measures have been used in multiple sclerosis (126), inflammatory bowel disease (127), and hospitalized patients (128) to study the prevalence of sleep problems.…”
Section: Promis Sleep Disturbance and Sleep‐related Impairmentmentioning
confidence: 99%